2018
DOI: 10.1002/lary.27205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the seventh and eighth edition american joint committee on cancer oral cavity staging systems

Abstract: 2c. Laryngoscope, 128:2351-2360, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 23 publications
4
54
1
3
Order By: Relevance
“…One more study from the United States by Cramer et al . concluded marginally improved prognostic ability for AJCC8 (0.699–0.704) …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One more study from the United States by Cramer et al . concluded marginally improved prognostic ability for AJCC8 (0.699–0.704) …”
Section: Discussionmentioning
confidence: 95%
“…In Mato's series, 22.8% were upstaged when their DOI was included in the pT classification and 29.2% were upstaged when ENE was included in the pN classification. Cramer et al . reported a 10% upstaging with the most significant increase seen in Stages II and III–IVB.…”
Section: Discussionmentioning
confidence: 97%
“…In a similar analysis of the NCDB by Cramer et al, compared the two AJCC staging systems using the NCDB in 39 361 patients with oral SCC, which showed that 10% of the patients were upstaged in the new classification with marginally improved prognostication value between the seventh and eighth edition (survival concordance index for pathological staging 0.699 and 0.704, respectively). 17 Their study looks at all stages I-IV of the disease when comparing stage migration including in the node positive neck. They also showed worsening HRs in the increasing pT categories based on the eighth edition AJCC.…”
Section: Discussionmentioning
confidence: 99%
“…The stage migration effect previously described can partially justify the results herein observed. Moreover, this phenomenon was more significant when restaging was performed according to pathological DOI (measured from the level of the basement membrane adjacent to normal mucosa to the deepest point of tumor invasion) rather than on the basis of clinical DOI (12).…”
Section: Validation?mentioning
confidence: 98%
“…By contrast, retrospective validation studies showed a similar DSS for T1 and T2N0 disease as identified by the last edition of the TNM staging system (4,10-12). This was another effect of the staging migration described above: since survival of T2N0 tongue SCC improved as more invasive cancers were clustered in Stage III disease, the existent gap between T1 and T2N0 scenarios was reduced in a parallel way (4,(10)(11)(12)17). At the same time, small cancers (<2 cm), infiltrating in depth more than 5 mm, migrated from T1 to T2.…”
Section: Validation?mentioning
confidence: 98%